2022
DOI: 10.3390/molecules27113618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wearing Surgical Face Masks on Gas Detection from Respiration Using Photoacoustic Spectroscopy

Abstract: Wearing surgical face masks is among the measures taken to mitigate coronavirus disease (COVID-19) transmission and deaths. Lately, concern was expressed about the possibility that gases from respiration could build up in the mask over time, causing medical issues related to the respiratory system. In this research study, the carbon dioxide concentration and ethylene in the breathing zone were measured before and immediately after wearing surgical face masks using the photoacoustic spectroscopy method. From th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Useful data are automatically recorded in real-time via a Test Point acquisition card under computer control. Further details about the experimental setup can be found also in our previously published papers [9][10][11][12][13][14][20][21][22][23][24][25][26].…”
Section: Co 2 Laser Photoacoustic Spectroscopy Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Useful data are automatically recorded in real-time via a Test Point acquisition card under computer control. Further details about the experimental setup can be found also in our previously published papers [9][10][11][12][13][14][20][21][22][23][24][25][26].…”
Section: Co 2 Laser Photoacoustic Spectroscopy Methodsmentioning
confidence: 99%
“…In contrast with other spectral systems, photoacoustic spectroscopy trace gas sensing technology is not to directly evaluate the change of light intensity and represent an indirect quantification process in the absence of background signal interference. For the reason that of these advantages, laser photoacoustic spectroscopy trace gas sensing is extensively solicitated in medical, industrial, environmental, monitoring, and other areas [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the concentration of individual immediately after wearing the surgical mask is 0.023 and 0.027 ppm after 1 h of wearing surgical mask. [174] 4.6.1. Autism Weakened social communications, interaction, and repetitive behavior in childhood caused by heterogeneous neurodevelopment disorder are known as an Autism spectrum disorder (ASD).…”
Section: Ethylenementioning
confidence: 99%
“…The results demonstrated that the concentration of individual immediately after wearing the surgical mask is 0.023 and 0.027 ppm after 1 h of wearing surgical mask. [ 174 ]…”
Section: Applications Of Ir Breath Analysis Over Biomarkersmentioning
confidence: 99%
“…The increasing popularity of PAS in recent years is attributable to its utilization of cost-effective components, such as 3D-printed measurement cells and cell phone microphones [11] , [12] , [13] . In view of photoacoustic breath monitoring in general, Popa et al studied the impact of wearing surgical face masks on the concentrations of the exhaled respiratory gas components CO 2 and ethylene [14] . For basic and applied breathomics (e.g., of unidentified VOC marker profiles) established gold standards like Gas-Chromatography Mass-Spectrometry (GC-MS) and real-time Proton-Transfer-Reaction Time-of-Flight Mass-Spectrometry (PTR-TOF-MS) represent the state of the art.…”
Section: Introductionmentioning
confidence: 99%